Book research quarterly - University of Scranton. Center for Book Research; Transaction Periodicals Consortium (Transaction Periodicals Consortium, Rutgers University, 1985)
Provides information about "the creation, publication, and distribution of books, past, present, and future"--V. 1, no. 1, p. [3].
Keywords: Books and reading : Periodicals; Book industries and trade : Periodicals; Book industries and trade; Books and reading; Boekwezen; United States : Book trades : Serials